2018
DOI: 10.15420/aer.2017.40.3
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Atrial Fibrillation: Theoretical Considerations and Practical Concerns

Abstract: Understanding the mechanisms responsible for driving AF is key to improving the procedural success for AF ablation. In this review, we look at some of the proposed drivers of AF, the disagreement between experts and the challenges confronted in attempting to map AF. Defining a 'driver' is also controversial, but for the purposes of this review we will consider an AF driver to be either a focal or localised source demonstrating fast, repetitive activity that propagates outward from this source, breaking down in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
(65 reference statements)
0
16
0
5
Order By: Relevance
“…The association of AF with the atrial Cx37 and Cx40 gene polymorphisms [35], as well as somatic mutations in GJA5 (encoding Cx40), have been identified in AF [36,37]. As a pulmonary veins isolation-based approach can resolve AF in 50%-70% of patients, it implies that other drivers of AF remain to be determined [38]. TH may be one of those drivers for AF.…”
Section: A Short Overview On Afmentioning
confidence: 99%
“…The association of AF with the atrial Cx37 and Cx40 gene polymorphisms [35], as well as somatic mutations in GJA5 (encoding Cx40), have been identified in AF [36,37]. As a pulmonary veins isolation-based approach can resolve AF in 50%-70% of patients, it implies that other drivers of AF remain to be determined [38]. TH may be one of those drivers for AF.…”
Section: A Short Overview On Afmentioning
confidence: 99%
“…81 Recent clinical review papers provide more details on electrical driver determination in AF. 82,83 Activation Versus Phase Mapping surface. We previously demonstrated that the spatial resolution of AF data can significantly affect the interpretation of the underlying AF mechanism, 84 which is a particularly important consideration when interpreting findings from low-resolution recording devices.…”
Section: Phase Mappingmentioning
confidence: 99%
“…[ 81 ] Recent clinical review papers provide more details on electrical driver determination in AF. [ 82 , 83 ]…”
Section: Cardiac Mapping Techniquesmentioning
confidence: 99%
“…The proposed mechanisms of AF dating to the early 1900s include focal automaticity, organised re-entry or multiple re-entrant wavelets. [6][7][8][9] Technological advances since then have allowed us to better conceptualise these principles. Focal triggers and drivers within the pulmonary vein muscle sleeves and in the antral regions of the pulmonary veins have been found to be the predominant mechanism of paroxysmal AF and wide-area PVI has yielded favourable results in patients with paroxysmal AF.…”
Section: Af Mechanismsmentioning
confidence: 99%
“…Focal triggers and drivers within the pulmonary vein muscle sleeves and in the antral regions of the pulmonary veins have been found to be the predominant mechanism of paroxysmal AF and wide-area PVI has yielded favourable results in patients with paroxysmal AF. 10 In addition to the pulmonary veins, other areas identified to harbour focal drivers include the superior vena cava and the coronary sinus. 11 While focal triggers may be the dominant mechanism in paroxysmal AF, multiple mechanisms often coexist in patients with persistent AF, with variable mechanisms accounting for the initiation and perpetuation of AF.…”
Section: Af Mechanismsmentioning
confidence: 99%